Material Transport Study into a Sag Mill by Dem Impact on the Inclination of Lifter - Gutierrez-Silva, A (Springer Science and Business Media, LLC, 2017)
This research studies the application of the discrete element method in the kinematics and dynamics of the flux of material and milling methods occurring inside a SAG mill of 40 x 26, working on normal operation conditions with a capacity of 120.000 ton/day. It is used a feeding granularity F80 of 150 mm at a critical speed rate of 72 %. Also, the study works with a DEM contact model between bodies which contains elastic and shock-absorber elements, the last ones have been varied to consider the presence of liquid inside the mill that changes the impact coefficients between the different surfaces to consider. The study begins with straight-line lifters, as they are used nowadays in the concentrators of the world. Then, there are proposed 4 cases which consider inclined lifters of 10, 15, 20, 25, 30 and 45°. The flux behavior will be studied, determining the exit flux and the wear produced on each case. With these results obtained it is possible to conclude whether it’s feasible to add inclined lifters or not. © Springer Science+Business Media Singapore 2017.